2020
DOI: 10.1111/cei.13540
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of galectin-10 release from eosinophils exposed to proliferating T cells

Abstract: Summary Galectin-10 is involved in the T cell suppressive activity of regulatory T cells and eosinophils alike. We have identified a subpopulation of T cell suppressive eosinophils that express CD16 on the surface and contain more galectin-10 compared with conventional CD16-negative eosinophils. Our main goal was to determine how the intracellular protein galectin-10 is released from eosinophils when exposed to proliferating T cells and if such release could be inhibited. Confocal microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The administration of CLCs together with innocuous antigen, that is, ovalbumin, was able to boost the antigen-specific T cell response in mice which was associated with increased antigen-specific antibody responses [17 ]. High levels of galectin-10 coming from a subset of CD16 + human eosinophils may also have a role in suppression of proliferating T cells [22].…”
Section: Charcot-leyden Crystals (Clcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of CLCs together with innocuous antigen, that is, ovalbumin, was able to boost the antigen-specific T cell response in mice which was associated with increased antigen-specific antibody responses [17 ]. High levels of galectin-10 coming from a subset of CD16 + human eosinophils may also have a role in suppression of proliferating T cells [22].…”
Section: Charcot-leyden Crystals (Clcs)mentioning
confidence: 99%
“…However, in its soluble form, galectin-10 plays important roles in eosinophil development [8] and it is conceivable that extracellular soluble protein may have as yet undescribed roles. One report demonstrated the presentation of galectin-10 on EETs to suppress Th2 cells [22] and galectin-10 bound to secreted vesicles may be taken up by other cells to initiate cell activation.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Yet another potential limitation is that anti-CD16 was used in gating of eosinophils to exclude neutrophils, which express a high level of CD16. Although this is a standard gating method and eosinophils in general do not express CD16 [33,34], CD16 may be induced on a subset of eosinophils in vitro by various mediators or detected on a subset of eosinophils in allergic rhinitis or asthma or even healthy subjects, according to some reports but not others [33][34][35][36][37][38][39][40]. We cannot rule out that a small proportion of eosinophils was gated out in our subjects.…”
Section: Plos Onementioning
confidence: 94%
“…In one such study, Lingblom et al demonstrated greater suppression of T-cell proliferation by CD16 hi eosinophils from healthy donors compared with CD16 lo eosinophils from the same donors 105 . This suppression was at least partly dependent on galectin-10 (Gal-10) released in extracellular DNA traps when eosinophils come into contact with activated T cells 111 . An area of ongoing controversy, especially in humans, is whether there are developmentally distinct populations of eosinophils that maintain their phenotype and function irrespective of their environment or whether the observed heterogeneity is entirely due to plasticity in response to external cues.…”
Section: Eosinophil Heterogeneity In Homeostasis and Immunitymentioning
confidence: 99%